MARULAK ARI TRADITION IN MANDAILING ETHNIC CULTURE REVIEWED FROM THE PERSPECTIVE OF ISLAMIC LAW (CASE STUDY OF MANDAILING NATAL REGENCY) - Muhammad Haddad Alwi Nasution; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (Pena Cendekia Insani, 2025)
The Marulak Ari tradition in Mandailing culture is the culmination of the wedding ceremony, involving customary law and connected to Islamic law. This research aims to analyze the tradition from an Islamic legal perspective, using a cultural anthropological approach. The methods used are field research and interviews with local traditional figures, as well as a comparative analysis between customary law and Islamic law. The research findings indicate that although the Marulak Ari tradition holds significant value in Mandailing culture, it contradicts the principles of Islamic law, particularly in the aspects of hifzh al-'aql (preservation of reason) and hifzh al-mal (preservation of wealth). Therefore, this research suggests the need for adjustments so that this tradition can continue to be carried out without contradicting Islamic teachings, by reducing elements that can be mentally and economically detrimental.